2017
DOI: 10.1016/j.chroma.2017.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of mesoporous silica layers on radially elongated pillars

Abstract: The present paper describes the application of a sol-gel procedure on radially elongated pillars (REPs) using tetramethoxysilane and methyltrimethoxysilane. After octadecylsilylation, the quality of the porous layered REP (PLREP) columns was evaluated by in-situ determination of migration velocities and band broadening of coumarin dyes with fluorescence microscopy in reversed-phase liquid chromatography. Based on the increase in retention due to the sol-gel process, an increase in accessible specific surface b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
(87 reference statements)
1
11
0
Order By: Relevance
“…Allowing for more than two different adsorption regimes will further increase the possible selectivity of the control strategy. Experimental demonstration of the efficiency of our theoretical concepts could for instance be obtained using micro-pillar array chips (Futagami et al, 2017;Callewaert et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Allowing for more than two different adsorption regimes will further increase the possible selectivity of the control strategy. Experimental demonstration of the efficiency of our theoretical concepts could for instance be obtained using micro-pillar array chips (Futagami et al, 2017;Callewaert et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The only drawback of these columns seems to be the price. They describe the application of a sol-gel procedure on radially elongated pillars (REPs) using tetramethoxysilane and methyltrimethoxysilane, with subsequent octadecylsilylation 115 . An increase in accessible specific surface by a factor of 112 compared to a nonporous REP was observed.…”
Section: Pillar Array Columnsmentioning
confidence: 99%
“…The mesoporous silica layer was prepared via the on-chip sol-gel processing procedure as described in [31]. In order to increase the layer thickness, the amount of TMOS/MTMS (VT/VM = 75/25) was increased by 30%, compared to the previously fabricated columns (cf.…”
Section: Preparation Of the Mesoporous Silica Layermentioning
confidence: 99%
“…Although the precisely controlled pillar shape, order, and interpillar distance enable high column efficiency, the nonporous nature of the pillars provides limited retention and sample loading capacities [26][27][28]. In order to overcome this issue, an interesting and feasible approach appears to be the use of sol-gel processing to deposit a silica layer on the pillars [17,[29][30][31]. In these studies, an increase in surface area compared to that of nonporous pillars was reported.…”
Section: Introductionmentioning
confidence: 99%